RTS,S/AS01 sebagai Vaksin Malaria Generasi Pertama - Komang Dendi Juliawan (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Malaria is an infectius disease caused by Plasmodium sp. The treatment for malaria with Artemisinin-based Combination Therapy (ACT) can cause resistance so a new effort is needed to reduce the morbidity of malaria. A better prevention method for preventing malaria is to use vaccines. The RTS,S/AS01 vaccine is the first generation malaria vaccine that has been applied in Ghana, Kenya and Malawi since early 2018. The vaccine consists of circumsporozoite protein antigen and hepatitis B. This vaccine has been shown to provide partial protection to children and has reach efficacy by 80%.